UPAYA GURU DALAM MEMINIMALISIR PERILAKU BULLYING DI SMA NEGERI 1 KOTA BIMA - AN-NISA FAJRIANI; Mohammad Mustari; M. Samsul Hadi; Muhammad Mabrur Haslan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe and analyze teachers' efforts to minimize bullying behavior.bullyingat SMAN1 Kota Bima. The background of the research is based on the high incidence ofbullyingverbal and relational in high school and the urgency of character education to prevent its psychosocial impacts. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, participant observation, and documentation. The data analysis technique used is the Miles and Huberman Model data analysis technique, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that: Teachers' efforts include structured planning through the integration of Pancasila values, religious teachings, and social-emotional education in the RPP and counseling modules; implementation of learning activities based on case study discussions,role‑play, and anti-projectsbullying; and comprehensive evaluation through observation of attitudes, reflective tasks, and counseling notes. Supporting factors for the success of the intervention are cross-field synergy of teachers, support for school policies, parental involvement, and active student participation. Inhibiting factors include uneven supervision in non-classroom areas, less harmonious family parenting patterns, and the influence of social media that facilitatescyberbullying..